Solid-state fabrication of nanostructured AlSb by electron beam heating process - Chaned Wichasilp (2018)
The utility of electron beam heating toward the synthesis of AlSb is reported. The solid-state electron beam heating using different electrical flow for the synthesis of AlSb was studied. The phase and morphologies were characterized using X-ray powder diffraction, and field-emission scanning and transmission electron microscopic techniques, and energy dispersive X-ray analyzer. Their electrical properties were also investigated using four-point probe resistivity measurement. ©2010 IEEE.